Electromigration damage in lead-free solder joints prepared using metallic nanoparticle doped flux / Muhammad Nasir - Muhammad , Nasir (2017)
Miniaturization of microelectronic devices and the associated increase in current density during operation raise concerns over electromigration (EM) damage in solder joints. This thesis focuses on the effects of Ni and Co nanoparticle (NP) doped flux on the microstructure, mechanical and electrical properties of the solder joints under EM. The EM tests were conducted on undoped SAC305 and NP-doped SAC305 solder joints. During EM, the electrical resistance was recorded for doped and undoped solder joints. After EM tests, the microstructure and mechanical properties were investigated. The microstructural and elemental analysis of the samples was conducted by field emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectroscopy (EDX). Crystallographic information on the samples was obtained by electron backscatter diffraction (EBSD). The mechanical properties of the samples were determined by a micro-tensile testing. To investigate the effects of EM on the microstructure, EM tests were run in an oil bath at a temperature of 80° C for a maximum time of 1128 h. A constant DC current was applied to achieve a current density of 1×104 A/cm2. To investigate EM effects on the mechanical and electrical properties, tests were performed for 192 h with a constant current density of 3×103 A/cm2 at 160° C. Results showed that Ni and Co atoms enter into the lattice of Cu6Sn5 leading to the formation of (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 at interfaces and in the matrix of the solder. Ni and Co thermodynamically stabilized the interfacial intermetallic compound (IMC) layers both at the anode and cathode sides. In the solder matrix, Ni and Co reduced the size of β-Sn grains and the thickness of IMC particles present in the eutectic region significantly. After EM testing, Ni and Co-NP doped flux substantially reduced the formation of cracks and voids at the cathode interface and improved the structural properties of the solder joint. The average IMC growth rates at the anode side of the Ni and Co-containing solder joints were about five and seven-times lower compared with that of the undoped samples. EBSD results revealed that Co and Ni NP-doped flux reduced the growth of interfacial IMC grains before and after EM. Ni and Co-doped IMC layers acted as a diffusion barrier for Cu atoms moving from the cathode to the anode side. No significant change in electrical resistance occurred in Co- and Ni-doped solder during EM tests carried out for a duration of 700 h. The electrical resistance of undoped solder joints increased during EM, and the samples failed before 500 h. Ni and Co-NP significantly improved the mechanical strength of as reflowed solder and reduced the degradation of strength after EM. The strength of undoped solder was degraded by 63% after EM, while Ni and Co-NP doped solder joints suffered a strength degradation of only 23.5% and 11.3%. After EM, Ni and Co-NP also improved ductility and fracture path of the solder. Overall, this report suggests that by adding Ni and Co-NP doped flux the reliability of the SAC305 solder joints under EM can be increased significantly.